Libraries, archives and information centres in rural community development (2003)
The role of libraries, archives and information centres in the provision of information for rural community development is examined. A survey of the information provison facilities in two rural communities in Oyo and Kogi states were carried out, and the problems encountered in the provision, dissemination and utilisation of the information are highlighted. It was discvered that facilities for information provision are inadequate and the methods of information dissemination too limited and often untimely. The prospects of information provision through traditional and modern means of information dissemination are discussed and suggestions for improving rural information provision are given